Ozone and carbon monoxide in the tropical trosphere, as seen by aircraft and satellite data; as seen by aircraft (IAGOS) and satellite (IASI) measurements - (:unkn) unknown (My University, 2023)
The overall objective of this thesis is to characterise ozone changes, and the characteristics of ozone (O3) and co distributions in the tropics. To do so, we used aircraft (IAGOS) and satellite (IASI) data. The evaluation of IASI using IAGOS, showed sensitivity of the O3 change to: i) the sampling, and ii) the vertical sensitivity of the satellite. The best agreement between IASI and IAGOS was in the partial column (700-200 hPa), where IASI retrievals are the most sensitive to O3. The average partial column O3 on a global scale increased by 0.4 DU (or 1.7 %) for 2018-2020 relative to 2008-2010, with the highest increase over South and SouthEast Asia (by 10 %). Using the observational data in combination with model data (SOFT-IO), we document the characteristics of tropospheric O3 and CO over the whole tropics for the last two decades. We explore the origin of the observed CO anomalies, and investigate transport processes driving the tropical CO and O3 distribution. Our study highlights the importance of anthropogenic emissions, mostly over the northern tropics. The highest O3 and CO tropical maxima are observed over Africa in the low troposphere during dry season (80 ppb of O3 at 2.5 km and 850 ppb of CO at 0.3 km over Lagos), mostly due to local anthropogenic emissions (60 %). Africa is the most important region in terms of export of emissions in the tropical troposphere. The second highest maxima are observed over Asia above the surface for CO, and in the free troposphere for O3, mostly due to local AN emissions. The only Asian cluster with O3 maxima in the low troposphere is South China (75 ppb at 2.6 km) due to local AN and BB emissions. The impact of the Asian emissions in the low and mid troposphere are limited on a regional or local scale. In the upper troposphere, the export of Asian emissions intensifies, mostly towards Arabia and northern tropical Africa. Last, the smallest low tropospheric CO maxima are observed over Arabian and Eastern Afr
Keywords: African Research